Continuous xylose fermentation by Clostridium acetobutylicum – Assessment of solventogenic kinetics. (September 2015) - Procentese, Alessandra; Raganati, Francesca; Olivieri, Giuseppe; Russo, Maria Elena; Salatino, Piero; Marzocchella, Antonio
Highlights: Clostridium acetobutylicum fermentation on xylose to produce butanol. Continuous fermentation in a CSTR equipped with a microfiltration unit. The kinetics of the butanol production has been assessed. The population of cells under solventogenic conditions has been assessed. Abstract: This work deals with the specific butanol production rate of Clostridium acetobutylicum using xylose – a relevant fraction of lignocellulosic feedstock for biofuel production – as carbon source. The tests were carried out in a CSTR equipped with a microfiltration unit. The dilution rate ( D ) ranged between 0.02 and 0.22 h −1 and the ratio R between the permeate stream rate and the stream fed to the reactor ranged between 14% and 88%. The biomass present in the broth was identified as a heterogeneous cell population consisting of: acidogenic cells, solventogenic cells and spores. The results were processed to assess the concentration of acidogenic cells, solventogenic cells and spores. The specific butanol production rate was also assessed. The max butanol productivity was 1.3 g L −1 h −1 at D = 0.17 h −1 and R = 30%. A comparison between the results reported in a previous work carried out with lactose was made.